Quality model proposal for educational material production in OCW sites - Piedra Pullaguari, N. (2011)
The contribution of the Massachusetts Institute of Technology (MIT), and its initiative OpenCourseWare (OCW), gave access to free course complete material, which is used by teachers in their classes, open for whoever requires teaching, learning and research material; this fact got to end up with geographic, social and cultural barriers. Hundreds of universities have joined this initiative and opened teaching contents used for students and made them available to be validated in academic pairs and teachers worldwide who bet for reputation and knowledge. This way emerges the need of developing a model which allows to guarantee the quality of OCW contents, where university takes advantage of its own structures, infrastructures, teachers and rest of elements, and incorporates it to the current educational trends where knowledge is free, open and ubiquitous. The model highlights eight relevant areas, taking into account the key elements to generate quality contents, using a social and constructivist approach, also, for its validation are used signatures which proactively help to identify strengths and improvable aspects of the courses. As a potential benefit from applying this quality model in superior educational institutions it is expected to improve production. © 2011 IEEE.